If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39x = 64x + 24 Reorder the terms: 39x = 24 + 64x Solving 39x = 24 + 64x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-64x' to each side of the equation. 39x + -64x = 24 + 64x + -64x Combine like terms: 39x + -64x = -25x -25x = 24 + 64x + -64x Combine like terms: 64x + -64x = 0 -25x = 24 + 0 -25x = 24 Divide each side by '-25'. x = -0.96 Simplifying x = -0.96
| 10x+12+4x-3= | | 5y-6+y+53=8y+50-5y | | 13t-2=3t+38 | | 11f=5f+36 | | 6(4x-8)=32 | | -8=2c-3c | | xy=120 | | 6-3(6-6x)=0 | | 3.2x+6.5=9.2+11x | | v^2-6v=20+2v | | (3+6)+4=3+(6+4) | | 1(x-4)=-5 | | 2(x+5.75)=15.275 | | 69.8x+42=65 | | 12/k=24k | | 120x+10=150x+4 | | 4x(2)-6x= | | 69.8+42=65 | | 2(x+3)+1=15 | | 56.80x+25.50=78x+100 | | 8x-15y=34 | | A=150*sqrt(3) | | 2(x+1)-5x=2x-8 | | F(x)=x/5-2x | | (2x-3y)(3x+6y)=0 | | 2x-5/6=6 | | (x-y)(x+2y)=0 | | x=2x^2+8x-16 | | (5-1)-2=5-(1-2) | | s-0.2=48 | | 6x+9=9-(3x-5) | | 6xy*5xy+5x= |